Surgical resection of a giant cardiac angiosarcoma and reconstruction of involved right heart structures: A case report - Blindaru, Andreea; Vasilescu, Alexandru; Danet, Andrei; Zimnicaru, Oana; Cristu, Maximilian; Tudorica, Stefan; Borjog, Tudor; Patrascu, Oana; Badiu, Catalin Constantin (Frontiers in Cardiovascular Medicine, 2023)
We present the case of a young woman without a medical history who presented with a giant right atrial, transtricuspid, and right ventricular mass and in a severe clinical state. Multimodal imaging raised the suspicion of primary cardiac angiosarcoma. Due to rapid hemodynamic and respiratory deterioration, we were forced to perform surgical removal of the mass with a concomitant reconstruction of the involved right heart structures, only 48 h after presentation. The postoperative course was uneventful, and the patient was discharged from the intensive care unit 2 days later. Radical surgical resection with reconstruction of the resected heart structures was the only possible salvage option for giant angiosarcoma, which led to hemodynamic instability. Followed by chemotherapy, this radical approach may prolong survival.